1979
DOI: 10.1111/j.1365-2052.1979.tb01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood groups of Nigerian cattle. Comparative aspects

Abstract: Cattle, red cell antigens as determined by a selected battery of 37 reagents characterizing genes at 10 major loci in 101 Zebu, 63 Ndama and 78 Muturu from Nigeria, have been compared with corresponding red cell antigens of a total of 257 Bos taurus cattle in Norway, the Netherlands, France, Spain, Hungary and USA. The Zebu cattle, represented by the three subtypes Gudali, Red Bororo and Shuwa Arab, showed the highest number of red cell factors. Ndama and Muturu cattle had a significantly lower number of blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Amino acid sequencing studies are needed to determine whether or not the Hb Bs of different breed groups are the same or different. The recent discovery that in special electrophoretic conditions Hb C in African Sanga breeds at gene frequencies as high as 0.4 (Braend, 1979). also Fig.…”
Section: Linkage Between Casein Locimentioning
confidence: 88%
See 1 more Smart Citation
“…Amino acid sequencing studies are needed to determine whether or not the Hb Bs of different breed groups are the same or different. The recent discovery that in special electrophoretic conditions Hb C in African Sanga breeds at gene frequencies as high as 0.4 (Braend, 1979). also Fig.…”
Section: Linkage Between Casein Locimentioning
confidence: 88%
“…Additional haemoglobin variants are more often found in Indian and African breeds than in European breeds. While the gene frequencies of these other haemoglobins 'are usually low, Hb D is present in some West African Dwarf Shorthorn breeds at gene frequencies as high as 0.4 (Braend, 1979).…”
Section: Linkage Between Casein Locimentioning
confidence: 99%
“…However, the FF2 gene has been shown to occur in British Friesian cattle (Hall & Ross, 1982;Ross & Larsen, 1981), and Stormont (1962) reported the finding of an allele reacting with anti-F, and anti-V, in American Charolais cattle. The F-and V-negative animals observed in studies of African and East Asian cattle (Osterhoff & Politzer, 1979;Abe, 1970;Carr et al, 1974;Braend, 1979;Fiorentini, Braend & Mzee, 1980) did not include tests for V,, N' and the additional factor (V') discovered in Edingburgh (Hall & Ross, 1982), and only the study by Osterhoff & Politter (1970) included anti-F,. They used anti-F, prepared in several laboratories and showed that some but not all of the Fand V-negative animals were F,-positive.…”
Section: Discussionmentioning
confidence: 99%
“…More recently the N' blood group factor was described as a member of the F blood group system (Grosclaude, 1966;Oldenbroek & Bouw, 1974), and at least one more antiserum has been reported detecting V', a factor of the F system (Hall & Ross, 1982). Thus in the original two-factor (F, and V,) two-allele system at least six antigens are recognized today, and studies in a variety of cattle breeds have revealed animals not reacting with the F and V reagents originally described (Osterhoff & Politzer, 1970;Abe, 1970;Carr et al, 1974;Braend, 1979;Fiorentini, Braend & Mzee, 1980). Furthermore, it has been observed that the factors V, and V, may not always behave as linear subtypes (Larsen, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…0 sterhoff & Politzer (1968) confirmed these findings in 1968 and named the allele FJ. The presence of eleven F-negative V-negative animals was reported in 1033 East African Zebu cattle by Carr et al (1974) and in two out of 101 West African Zebu by Braend (1979). The first report that F-negative V-negative cattle existed in breeds of Western Europe (that were not of African origin) was given by Dabczewski (1969) who found the negative phenotype in 8.7 % of253 animals of the Kerry breed in Ireland.…”
Section: Introductionmentioning
confidence: 95%